The role of mechanical engineering in industry: Review and bibliometric analysis - Al-Obaidi, Abdulkareem Sh. Mahdi; Husaeni, Dwi Fitria Al; Setiyo, Muji; Nandiyanto, Asep Bayu Dani (Mechanical Engineering for Society and Industry, 2024)
Innovation has shown progress in many sectors, including mechanical engineering which is closely related to industry. Through a literature survey and bibliometric analysis of 1,920 articles sourced from the Scopus database from 2015 to 2024, this paper investigates the role that mechanical engineering plays in industrial progress. The analysis uses VOSviewer for network visualization, overlay, and density maps. According to the findings, mechanical engineering has significantly advanced several important areas, including advanced manufacturing processes, Industry 4.0 and digital transformation, sustainability and circular economy, educational advancement, use of new technologies, and biotechnology innovation. Some of the key findings of this review include the use of digital twins and integrating cyber-physical systems, the use of large-scale 3D printing technology, and the use of sustainable production methods in industry. According to the analysis, the number of publications and citations has increased, with a slight decrease during the COVID-19 pandemic. Visualizing this bibliometric map helps understand current trends, identify potential research areas, and highlight relationships between research issues.